2007
DOI: 10.1016/j.euroneuro.2006.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of risperidone on dopamine receptor subtypes in developing rat brain

Abstract: The atypical antipsychotic risperidone is often prescribed to pediatric patients with neuropsychiatric disorders, though its effects on the developing brain remain unclear. Accordingly, we studied the effects of repeated treatment of risperidone on dopamine receptors in brain regions of juvenile rat. Levels of dopamine receptors (D 1 , D 2 , D 3 , D 4 ) in forebrain regions of juvenile rats were quantified after 3 weeks of treatment with three different doses of risperidone (0.3, 1.0 and 3.0 mg/kg) and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 41 publications
3
46
0
Order By: Relevance
“…Positron emission tomography (PET) studies which examined striatal D2 receptor levels in antipsychoticnaive schizophrenia patients reported inconsistent results, as one study reported a significant elevation of striatal D2 receptors (14) while two other studies failed to detect significant changes in striatal D2 receptors in drug-naive patients diagnosed with schizophrenia (15,16). Repeated treatment of laboratory animals with various first-and second-generation antipsychotic drugs altered concentrations of different DA receptor subtypes in cortical, limbic and extrapyramidal brain regions of mature and developing rats (17)(18)(19)(20).…”
Section: Dopamine/glutamate Hypothesis Of Schizophreniamentioning
confidence: 99%
“…Positron emission tomography (PET) studies which examined striatal D2 receptor levels in antipsychoticnaive schizophrenia patients reported inconsistent results, as one study reported a significant elevation of striatal D2 receptors (14) while two other studies failed to detect significant changes in striatal D2 receptors in drug-naive patients diagnosed with schizophrenia (15,16). Repeated treatment of laboratory animals with various first-and second-generation antipsychotic drugs altered concentrations of different DA receptor subtypes in cortical, limbic and extrapyramidal brain regions of mature and developing rats (17)(18)(19)(20).…”
Section: Dopamine/glutamate Hypothesis Of Schizophreniamentioning
confidence: 99%
“…Motor activity was recorded for the entire 90-min testing session. One day after the challenge test (~P 52), rats were sacrificed by live decapitation and their brains were removed for further analysis [37]. …”
mentioning
confidence: 99%
“…There may be some support for these hypotheses. For example, increased D1 and NMDA receptor binding in the NAc was observed selectively with chronic adolescent risperidone treatment at 24 hours after this regimen (Moran-Gates et al 2007). Some changes, for example, increased D2…”
Section: Apdsmentioning
confidence: 99%
“…I also observed no change in dopamine receptor expression. A more sensitive technique such as radioligand binding which can also give a read-out of functional receptor activity may provide more information on risperidone-induced changes in dopamine receptors (Moran-Gates et al 2007). …”
Section: Striatal Neurochemical Changes In Adolescents and Adults Folmentioning
confidence: 99%
See 1 more Smart Citation